2016
DOI: 10.1186/s40173-016-0076-7
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in euro area Beveridge curves and their determinants

Abstract: This paper analyses euro area Beveridge curves at the euro area aggregate and country level over the past 25 years. Using an autoregressive distributed lag model, we find a significant outward shift and flattening of the euro area Beveridge curve since the onset of the crisis, but considerable heterogeneity at country level. We test for factors underlying these developments using the local projection method of Jordà (Am Econ Rev 95(1): 2005). Skill mismatch and high shares of construction workers, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
6
1
1
Order By: Relevance
“…The Czech economy struggled with short growth and recession periods, which had a major impact on the Beveridge curve shifts that are relatively difficult to trace. This is in accordance with a study of Bonthuis, Jarvis and Vanhala (2016). One of the main findings is that job vacancy rates have improved in many countries, but unemployment rates have remained relatively high or surprisingly have kept rising.…”
Section: Resultssupporting
confidence: 91%
“…The Czech economy struggled with short growth and recession periods, which had a major impact on the Beveridge curve shifts that are relatively difficult to trace. This is in accordance with a study of Bonthuis, Jarvis and Vanhala (2016). One of the main findings is that job vacancy rates have improved in many countries, but unemployment rates have remained relatively high or surprisingly have kept rising.…”
Section: Resultssupporting
confidence: 91%
“…This paper shows that there is a significant shift in the Beveridge curve of the Austrian labor market. While the studies by (Bonthuis et al 2013) or (Bonthuis et al 2015) suggested that there was no shift of the Beveridge curve in Austria after the crisis, we show that a statistically significant shift simply took place later than in other European countries (such as Spain, France, and Portugal).…”
Section: Discussioncontrasting
confidence: 71%
“…In Austria, the Beveridge curve did not seem to change after 2009, contrary to economies struck harder by the financial crisis such as Greece, Italy, Spain, France, and the Eurozone as a whole (see Bonthuis et al (2015)). However, since 2013, a new development can be observed in Austria: rising unemployment rates unaccompanied by changes in vacancy rates.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Utdannelses-eller kvalifikasjonsmessig og regional mistilpasning anses å vaere viktige årsaker til ineffektive arbeidsmarkeder i mange OECD-og euro-land, spesielt etter finanskrisen i 2008, jf. Haincourt & Mogliani (2012), Zimmer (2012), Morgado, Sequeira, Santos, Ferreira-Lopez & Reis (2016) og Bonthuis, Jarvis & Vanhala (2016).…”
unclassified